Copyright and multimedia products : a comparative analysis - Stamatoudi, Irini A. (Cambridge studies in intellectual property rights., 2004)
Although multimedia products are highly successful, they are inadequately protected by existing copyright schemes. Stamatoudi considers existing legislation, and chapters treat topics including databases, audiovisual works and computer programs; finally, she offers a model for a European legislative solution. This will interest academics, students, practitioners and copyright policy makers.